Introductions and transfers of species by ballast water in the Adriatic Sea. (October 2019) - Gollasch, Stephan; Hewitt, Chad L.; Bailey, Sarah; David, Matej
Abstract: Following the Editorial addressing the BALMAS project, we open the ballast water management special issue for the Adriatic Sea by providing background information on non-indigenous species and the mechanisms (vectors) of transport. Problems allocating introduction mechanisms for various species with certainty are described; in general, key introduction mechanisms are shipping, with ballast water and biofouling as dominant vectors, and aquaculture activities. The dominant mechanisms for introduction may differ through time, between regions and across species. We highlight ballast water as the focus of an international convention to prevent future introductions, reviewing management options and suggesting future research needs. This assessment is not restricted in application to the Adriatic Sea, but is applicable to other coastal waters. Results of such future work may contribute to the experience building phase planned by the International Maritime Organization for a harmonised implementation of the Ballast Water Management Convention. Graphical abstract: Unlabelled Image